Determinants of Stunting among Children Under Five Years of Age: Evidence from Pakistan Demographic and Health Survey - Maria Aslam, Sehar Saleem, Seyab Yasin, Sana Nazir, Soha Waseem Chaudhary, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the factors that influence the stunting level of children under the age of five years in Pakistan. Methods: This study was conducted using Pakistan Demographic and Health Survey (PDHS) 2017-2018 during 2020-2021.The response variable comprised two categories: stunted and not stunted. In this study the demographic and socioeconomic factors affecting stunting are region, birthplace, preceding birth interval, women's education level, husband\partner`s education level, women's age, breast feeding, size of child at birth, total child ever born, type of place of residence, frequency of listening to the radio, sources of drinking facilities, and antenatal visits. A binary logistic regression model was applied to access the relationship between stunting with potential demographic and socioeconomic factors. Results: The binary logistic regression model identified that the significant factors for stunting of children in the regions of Pakistan are: Punjab (OR=.311, CI; 0.104, 0.934),KPK(OR=0.278,CI; 0.091,0.853), mother education(secondary OR=2.671,CI; 1.025,6.959),father education (Secondary OR=0.370, CI;0.146, 0.938),breastfeeding (1-year OR=0.197, CI; 0.056,0.689), child size (larger than average OR=0.113, CI; 0.020,0.646) and (average OR=0.212, CI;0.047,0.962). Practical implication: Identifying the determinants of stunting can lead to improved health outcomes for children, including reduced mortality rates, better cognitive development, and improved physical growth. Conclusion: This study discovered that stunting in Pakistan can be reduced by improving the education level of parents, proper breastfeeding, and proper diet during pregnancy duration. Keywords: Stunting, Binary logistic model, children, parent’s education